2014
DOI: 10.1021/je401075p
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Adsorption on Polyethylenimine-Functionalized SBA-15 Mesoporous Silica: Isotherms and Modeling

Abstract: SBA-15 mesoporous silica was functionalized with polyethylenimine and was used as a substrate for CO 2 adsorption. The synthesized material, denoted SBA-15-PEI, was characterized by means of X-ray diffraction, thermogravimetric analysis, and N 2 adsorption/desorption at 77 K, in order to prove that polymer chains efficiently filled the pores of functionalized samples. CO 2 adsorption isotherms on SBA-15-PEI were evaluated at T = (298, 313, 328, and 348) K for pressures up to 100 kPa by means of a volumetric te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 40 publications
2
47
1
Order By: Relevance
“…The whole activation energy is 73.02 kJ/mol, in accordance with the result obtained by thermogravimetricanalysis (70.56 kJ/mol) as presented in Table 2. The values obtained here are larger than the values obtained by Liu et al [27], but smaller than the values calculated by Sun et al [28]. However, the actual rate-limiting step for CO 2 adsorption could not be obtained by Avrami's model, which needs further investigation.…”
Section: 3desorption Mechnismscontrasting
confidence: 79%
See 1 more Smart Citation
“…The whole activation energy is 73.02 kJ/mol, in accordance with the result obtained by thermogravimetricanalysis (70.56 kJ/mol) as presented in Table 2. The values obtained here are larger than the values obtained by Liu et al [27], but smaller than the values calculated by Sun et al [28]. However, the actual rate-limiting step for CO 2 adsorption could not be obtained by Avrami's model, which needs further investigation.…”
Section: 3desorption Mechnismscontrasting
confidence: 79%
“…Currently, a lot of kinetic models are proposed to describe the experimental data. For example, Langmuir model [24,25], Langmuir-Freundlichmodel [26,27], pseudo-first-order [28], pseudo-second-order [29], and Avrami's model [21,30,31]. Kinefuchi et al [30] found that Avrami's fractional-order kinetic model could describe the desorption process well.…”
Section: Desorption Kineticsmentioning
confidence: 99%
“…This is a model often used to deal with microporous materials, such as zeolites, for which a pore filling process controls adsorption phenomena. Unlike other theoretical isotherms, such as the Sips [34][35][36][37][38] or Toth one [39], the DA isotherm does not rely on entirely empirical expressions to describe the dependence of the maximum adsorption capacity and of the heterogeneity coefficient on temperature. Moreover, the DA model well describes the behavior of adsorbates, such as water vapor, which are characterized by strong molecular lateral interactions.…”
Section: Theory/calculationmentioning
confidence: 99%
“…In this work, we synthesized a hierarchical zeolite X with mesoporosity (Meso-13X) and attempted to make use of the mesoporosity to incorporate increased and better dispersed amine species inside its pore structure. Polyethylenimine (PEI) was chosen as the amine source, which was found to greatly enhance CO 2 capture when supported on mesoporous silica [18][19][20][21][22][23]. The effectiveness of PEImodified Meso-13X (Meso-13X-PEI) as a CO 2 adsorbent was tested in terms of its adsorption capacity, selectivity and stability.…”
Section: Introductionmentioning
confidence: 99%